The status of international law in the Malaysian municipal legal system: creeping monism in legal discourse - Shuaib, Farid Sufian (International Islamic University Malaysia, 2008)
This article revisits the status of international law in the Malaysian municipal legal system and considers whether monism is the doctrine or the preferred doctrine in relation to the proper place of international law in Malaysia. This revisit is necessary because of the tendency in some legal writings and legal opinions to take a cavalier approach in using international instruments to dictate the content of municipal law. While observing the ascendancy of international institutions and instruments in determining international and national obligations, it is necessary to take stock of things to maintain a balance between being sovereign and being a member of the global neighbourhood.